Influence of Tangential Displacements on the Dynamic Buckling of Viscoplastic Cylindrical Shells - Jóźwiak, S.; Wojewódzki, W. (Engineering Transactions, 1982)
A theory of dynamic buckling is developed for viscoplastic cylindrical shells subjected to uniform radially inward impulses. The influence of tangential displacements on the magnitude of radial displacement, buckling mode and critical impulse is investigated. Asymmetrical and axisymmetrical mode of buckling are considered. It is shown that the asymmetrical mode occurs, what is in accord with the experimental observations reported in the literature.